How professionals talk about complex cases: a critical discourse analysis. Issue 2 (9th January 2014) - Hood, Rick
Abstract: This paper reports on a qualitative study of child protection in the UK. The research involved children's practitioners from a range of agencies, including social care, education, health and youth offending, who were asked about working together on complex child protection cases. The aim was to explore how participants talked about complexity in these cases, in order to deconstruct influential perspectives on interprofessional working. Interview transcripts were analysed using critical discourse analysis, a qualitative method that examines patterns of language use in relation to social structures of power and control. The findings identified three overall perspectives: clinical, expert system and relation‐centred approaches, which practitioners combined in various ways. These perspectives have a bearing on how the 'team around the child' is conceptualized in discourse about child protection. The paper links these findings to the assumptions of predictability and control currently embedded in policy and practice guidance, and explores their implications for social workers and other children's practitioners.